Making occupational therapy research visible: amplifying and elevating the contribution and impacts. (April 2021) - Jones, Natalie Louise; Cooke, Jo; Holliday, Judith
Researchers are increasingly required to be accountable for research findings and demonstrating outputs from research findings. A review of occupational therapy research promotes the use of impact assessments to make visible research outcomes (Sainty, 2013 ). However, not all impacts are visible to those who are trying to balance the management of clinical services, along with delivering research and enabling clinical academic careers. Nationally and internationally research organisations are increasingly demanding researchers to be open, accountable and transparent in demonstrating the value research adds to healthcare organisations and the way the research impacts are reported are increasingly scrutinised. To capture research impacts we need to have a suitable measure which provides meaningful data for the context and type of project. Research impact frameworks enable organisations and researchers to tell their research impact stories by providing a systematic structure for organising evidence, achievements and case studies. This editorial shares the experience of developing a research impact tool for capturing research impacts within an organisation and discusses the importance of using research impact tools to amplify and elevate outcomes of clinical research in occupational therapy.